Media Development of Video Learning in the Social Discussion of Social Problems in Social Science (IPS) Lesson of Class IV in Public Elementary School (SDN) 135911 Tanjungbalai Academic Year 2018-2019 - Mustafa Habib; Ibnu Hajar; Deny Setiawan (BIRCU, 2019)
In material social problems, students have difficulty digesting and identifying social problems in their surrounding environment. One alternative so that learning can take place efficiently and easily understood is to use learning video media. The subjects of this study were all fourth grade students of Public Elementary School (SDN) 135911 Tanjungbalai. The result shows that the development of learning video media was validated by 3 experts namely material experts, linguists and media experts. Appraisal by material experts obtained a value with a very good category (93%), the assessment by linguists obtained a value with a very good category (92.22%) and the assessment by media experts obtained a value with a good category (87.37%). A total of 9 students (45%) gave a very good assessment of the learning videos developed and as many as 11 students (55%) gave a good assessment of the learning videos developed and the learning video media were considered to be feasible to be developed.